Punitive symbolism in the prevention and repair of damages derived from protective measures - Bermúdez Tapia, Manuel (2020)
The context of social violence affects the family sphere, generating a disproportionate increase in statistics in recent years, rendering the actions of the State sterile through its public entities. Public policies to control acts of violence within families are being discredited and the real reason for this failure details a fundamental defect: the State is assuming that violence is fought through legal, judicial and state actions, thereby avoiding addressing the true origin of extreme violence in the country. As a result of this situation, legislation is observed that is constantly modified, establishing more coercive and punitive levels but without addressing the facts that cause situations of violence, aggressiveness and lack of control of people in their family relationships, because in addition These have been transformed in recent years, generating a symbolic and dysfunctional regulatory system that negatively conditions the magistrates, because they are the ones who assume the social responsibility of dealing with cases of domestic violence.